The Place of the Capital’s Main Square Kızılay in the Social Memory of the Citizens - Varol, Çiğdem; Sat, N. Aydan; Yenigül, Sevinç Bahar; Gürel Üçer, Z. Aslı (ICONARCH International Congress of Architecture and Planning, 2017)
A city’s main square is the unique identity of that city. Squares form the focus of social integration and social learning processes via the spatial functions and architectural identity they created. Squares are the hearts of cities, where economic, social and cultural activities take place. As being one of the open public places in the city, squares have various symbols that form their identity and bring people together to exhibit their way of living. At these places, individual-society relationships are shaped and the opportunities of socializing by active and passive communication styles emerge. Beginning with the 1950s in Turkey, cities have grown steadily with the increasing development, thus increasing population in cities. With this process, urban spaces have faced with the pressure of economic rationality in design. They have forgotten the traditional images of Anatolian cities like; square, atriums and human scale, and city culture like; urbanity, awareness of being urban, urban values, customs and traditions, and they have transformed into ordinary spaces without carrying an identity. This process has also affected public squares and from being the main focus of everyday life reflecting the personality and the identity of the city throughout the history, they have transformed into vehicle squares and parking places. Within this context, the aim of this study is to explore the changing meaning of Kızılay Square, which has an important place in the formation of the Capital Ankara’s identity, in relation with the social, economic and spatial changes since the foundation of the Turkish Republic. To reach this aim, an oral history method is held to investigate the changing meaning of Kızılay Square in the memories of the citizens. In this context, face to face interviews have been realized with the inhabitants (academicians and specialists, shopkeepers and daily users) testified the transformation of Kızılay Square. By this oral history study, which integrates the ordinary people and everyday life to the field of urban history apart from the written historical documents, it is aimed to reach some findings related to the place of Capital’s main square in the memories of the citizens.Public Spaces